Analisis Efektivitas Dan Kontribusi Pajak Reklame Dan Pajak Restoran Terhadap Pendapatan Asli Daerah Kota Bogor - Eka Yuniati; Yuliandi Yuliandi (Institut Bisnis dan Informatika Kesatuan, 2021)
Local Revenue is a source of original revenue derived from the potential of the region it self. Local Revenue is often used as an indicator of a region's progress. If the original income of a region is high, the economy of the area is considered advanced. The higher the Local Revenue received, the less dependency between the Regional Government on the Central Government. The largest revenue potential for Local Revenue is generated from local tax collection. One of the potential local tax revenues in Bogor City is the advertisement tax and restaurant tax. The purpose of this study was to determine the level of effectiveness and contribution of advertisement tax and restaurant tax to Local Revenue in Bogor City and to find out the efforts made by the Bogor City Regional Revenue Agency in increasing its local tax revenue. The research method used is descriptive qualitative method. The result of this research is that the effectiveness of the advertisement tax and restaurant tax collection in Bogor City has been very effective, proven by the average advertisement tax effectiveness ratio of 104.06% and restaurant tax of 103.93%. The contribution of advertisement tax and restaurant tax to Local Revenue in Bogor City is still not good, as evidenced by the average advertisement tax contribution ratio of 1.43% including very poor criteria, and the average restaurant tax contribution of 12.99. % is in the poor criteria. Efforts made by the Bogor City Regional Revenue Agency in increasing advertisement tax revenue and restaurant tax are by collecting taxpayer data, checking tax rates, monitoring tax administration, and building communication and establishing closeness with the community. Keywords: Effectiveness, Contribution, Advertising Tax, Restaurant Tax, Local Revenue